The necessity and significance of basic design lesson in fine arts high schools - Kavuran, Tamer; Polat, Bülent (My University, 2016)
Art comprises every way that leads to a person’s revealing any perceived situation. As for design, it is an image which is generated in the mind either of an object with a plan or in the object’s generation stage. In arts education, in order to direct the intended creativity light, certain methods are needed to be taught. These methods can be introduced with the Basic Design Lesson. The purpose of the Basic Design Lesson is to gain skills of recognition of techniques, tools and materials which are needed to be used in the beginning of the design stage until the end and regulation of these instruments to attain an appearance. This lesson aims to provide the means of discipline for the individuals who will make a design with accurate observation, research, and easy problem-solving skills. Additionally, Basic Design Lesson is an important tool for individuals to develop skills under the guidance of certain rules and with an artistic disposition, providing them with vision and awareness of visuality and use these together accordingly. The sooner an individual who is educated in arts meets the required basic training, the quicker this individual will reveal the talent inside, advancing in the development and reflect his/her own light. Due to lack of Basic Design Lessons in existing Fine Arts High Schools in Turkey, the graduates of these schools may have to face difficulties in design on their future educations. However, it’s obvious that the sooner the basis of design is established, the better it becomes. The lack of Basic Design Lessons in Fine Arts High Schools in Turkey constitutes the problem of this study. The study is attempted to be described via scanning of indexes and abstracts of scientific publications. In the light of the findings acquired from the scientific data, the result of the necessity of the Basic Design Lesson is deduced and relevant suggestions are made.

Sanat eğitimi yaratıcılık eğitimidir.Okutulan derslerde genel olarak öğrencilerin yaratıcılığını ön plana çıkarmaya çalışmak,güzel sanatlar eğitimi için bir ilke olmalıdır.Genel olarak tasarım ve mimarlık gibi fakültelerde okutulan temel tasarım dersini alan öğrencilerin,güzel sanatlar liselerinde böyle bir dersle karşılaşmadıkları için yaşadıkları sorun azımsanamayacak kadar büyüktür. Yaratıcılığın içinde, sanatta yeni ve özgün bir şey yaratmak bütünselliğine ulaşmak için algı da önemli rol oynar Wernher Von Braun “bilinen şeyleri, yeni biçimde kullanmak, şimdiye kadar olduğundan başka biçimde birleştirmektir” diyor. Bundan şu anlaşılıyor ki yaratıcılık üzerine araştırma yapanlar farklı sözcükler de kullansalar içerik olarak birbirine yakın tanımlar yapıyorlar. Temel tasarım dersinde kullanılan materyaller aslında günlük hayatta hemen herkesin karşılaştığı objelerdir.Amaç bu tarz bilinen objelerden düşüncelerinizi yansıtacak yeni bir şey yaratmaktır.Ve bu aktif hayal gücünü ve yaratıcılığı geliştirmektedir.Ancak Güzel sanatlar liselerinde böyle bir dersin yer almaması bir sorundur.Bu sorunun nasıl çözüleceği ile ilgili kapsamlı bir araştırma yapılmış ve çözüm odaklı yapılması gerekenler sıralanmıştır.
Güzel sanatlar liselerinde temel tasarım dersinin gerekliliği ve önemi
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Creativity; Fine arts high school; Basic design; Güzel sanatlar lisesi; Sanat; Temel tasarım; Yaratıcılık; Özgünlük